Interactive Marketing Practices and Market Performance in Soft Drinks Industry: An Empirical Study on Competitive Advantage As a Mediator - Nimusima, Pereez; Aryatwijuka, Wilbroad; Emmanuel, Erem; Charles, Kaggwa; Mbabazi, Olivia; Rwakihembo, John (Journal of Strategic Management, 2023)
Purpose: To what extent does competitive advantage mediate the relationship between interactive marketing practices and market performance? In attempt to respond to this question, this study was conducted with the aim of examining the mediating role of competitive advantage on the interactive marketing practices market performance relationship in the soft drink industry context. Methodology: A cross-sectional research design was taken on a sample of 322 soft drink manufacturing enterprises in the city of Kigali. The unit of inquiry for the quantitative study were the sales, accounting, finance, marketing and communication managers whereas chief executive officers were the unit of inquiry for the qualitative study. The study used both questionnaire and interview guide to collect data. Path analysis, MedGraph v3.xlsm and Hierarchical regression were used to test the model. Findings: Study findings show that performance of soft drink enterprises is positively associated with interactive marketing practices. It was observed in this study also that competitive advantage partially mediates this relationship. Practically the four conditions for mediation were met as suggested by Baron and Kenny, (1986). Firstly, we observe that there was a significant direct effect of Interactive marketing practices on market performance (=.270; p<.05). Secondly, Interactive marketing practices and competitive advantage have a significant relationship (=.400; p<.05), and thirdly, the observed coefficient of the mediator (competitive advantage) is significant as seen in the regression model 3 (=.396; p<.05). It is observed, finally, that the absolute effect of Interactive marketing practices on market performance is smaller in regression model 3 (=.157; p<.05) than in regression model 2 (=.270; p<.05).This confirm the mediation effects of competitive advantage. Further still a ratio index of 41.9% was observed an indication that competitive advantage reduces the relationship between interactive marketing practices and performance by 41.9% in Kigali city soft drink enterprises. Recommendations: In line with this confirmed mediation effects, managers are reminded to allocate sufficient resources to customer intimacy, product leadership and operational excellence as specific competitive priorities if they are to attain better market performance results. The study is of a theoretical importance as it empirically confirm the mediating role of competitive advantage in the interactive marketing practices-market performance relationship in a soft drink industry context. The imperative for practitioners to sufficiently attend to operational efficiency, customer intimacy and product leadership is reiterated on in this study.